Pathogenesis of Focal Segmental Glomerulosclerosis - Beom Jin Lim; Jae Won Yang; Woo Sung Do; Agnes B. Fogo (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Focal segmental glomerulosclerosis (FSGS) is characterized by focal and segmental obliteration of glomerular capillary tufts with increased matrix. FSGS is classified as collapsing, tip, cellular, perihilar and not otherwise specified variants according to the location and character of the sclerotic lesion. Primary or idiopathic FSGS is considered to be related to podocyte injury, and the pathogenesis of podocyte injury has been actively investigated. Several circulating factors affecting podocyte permeability barrier have been proposed, but not proven to cause FSGS. FSGS may also be caused by genetic alterations. These genes are mainly those regulating slit diaphragm structure, actin cytoskeleton of podocytes, and foot process structure. The mode of inheritance and age of onset are different according to the gene involved. Recently, the role of parietal epithelial cells (PECs) has been highlighted. Podocytes and PECs have common mesenchymal progenitors, therefore, PECs could be a source of podocyte repopulation after podocyte injury. Activated PECs migrate along adhesion to the glomerular tuft and may also contribute to the progression of sclerosis. Markers of activated PECs, including CD44, could be used to distinguish FSGS from minimal change disease. The pathogenesis of FSGS is very complex; however, understanding basic mechanisms of podocyte injury is important not only for basic research, but also for daily diagnostic pathology practice.